2022
DOI: 10.1089/neu.2021.0408
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging Reveals Elevated Diffusivity of White Matter Microstructure that Is Independently Associated with Long-Term Outcome after Mild Traumatic Brain Injury: A TRACK-TBI Study

Abstract: Diffusion tensor imaging (DTI) literature on single-center studies contains conflicting results regarding acute effects of mild traumatic brain injury (mTBI) on white matter (WM) microstructure and the prognostic significance. This larger-scale multi-center DTI study aimed to determine how acute mTBI affects WM microstructure over time and how early WM changes affect long-term outcome. From Transforming Research and Clinical Knowledge in Traumatic Brain Injury (TRACK-TBI), a cohort study at 11 United States le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 35 publications
3
11
0
Order By: Relevance
“…As such, decreased FA, decreased AD and increased RA would be expected in CTE due to decreased white matter integrity. These findings have been demonstrated in mTBI, and even had prognostic value [39] [47] . A post-mortem tissue DTI analysis of patients with confirmed CTE-NC by Holleran et al demonstrated associations between decreased FA and reduced white matter integrity [38] .…”
Section: Investigational Imaging Modalitiessupporting
confidence: 54%
“…As such, decreased FA, decreased AD and increased RA would be expected in CTE due to decreased white matter integrity. These findings have been demonstrated in mTBI, and even had prognostic value [39] [47] . A post-mortem tissue DTI analysis of patients with confirmed CTE-NC by Holleran et al demonstrated associations between decreased FA and reduced white matter integrity [38] .…”
Section: Investigational Imaging Modalitiessupporting
confidence: 54%
“…Another method to reduce the limitations of multimodal imaging is the creation of longitudinal prospective multi-institutional studies to standardize imaging techniques and link acute imaging results with long-term functional outcomes. One such example is the TRACK-TBI study, which has leveraged this model to uncover early multimodal imaging markers in mTBI that predict long-term outcomes [ 193 ]. Furthermore, the data generated by studies like TRACK-TBI can be used to train, validate, and test machine learning models to uncover prognostic insights into TBI physiology that could be used to guide treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Another method to reduce the limitations of multimodal imaging is the creation of longitudinal prospective multi-institutional studies to standardize imaging techniques and link acute imaging results with long-term functional outcomes. One such example is the TRACK-TBI study, which has leveraged this model to uncover early multimodal imaging markers in mTBI that predict long-term outcomes [156]. Furthermore, the data generated by studies like TRACK-TBI can be used to train, validate and test machine learning models to uncover prognostic insights into TBI physiology that could be used to guide treatment.…”
Section: Imaging-and Neuromonitoring-guided Treatmentmentioning
confidence: 99%